Music in education: a possibility to be expanded in the national scenario (Research, Society and Development, 2020)
Through many educational perspectives that we are inserted in, this article aims to verify the use of music as a pedagogical tool in basic education. For this, a bibliographic search was carried out, using content analysis as the main work methodology. This analysis used as basis the articles published in journals registered in the Capes database with qualis A1, in the education and teaching divisions, from 2013 to 2016. We found 42 articles, published in 32 different journals involving music in all areas of knowledge. The vast majority of productions were by national authors. Thus we can conclude that music, despite showing a promising character in education, and although it has permeated the educational system since the last century, it is still not used effectively to articulate and promote transdisciplinary teaching and learning in an effective way, as pedagogical resource.